Morpheme-internal recursion in phonology - Nasukawa, Kuniya (Studies in generative grammar ;, 2020)
Generative phonology aims to formalise two distinct aspects of phonological processes: the functional and the representational. Since functions operate on representations, it is clear that the functional aspect is influenced by the form of representations, i.e. different types of representation require different types of rules, principles or constraints. This volume examines the representational issue in phonology and considers what kind of representation is most appropriate for recent models of generative phonology. In particular, it provides the first platform for debate on the place of morpheme-internal structure and on the formal status of phonology in the language faculty, and attempts to identify phonological recursive structure as a means of capturing frequently observed processes.